The development of the Buddhachinaraj electronic medical record program, In-patient ward, Buddhachinaraj Hospital Phitsanulok - Sathienvantanee, Visithi; Indee, Ampai; Chiangtha, Ratanaporn; Wichitsakulcha, Thanawit (Journal of the Thai Medical Informatics Association, 2023)
Buddhachinaraj Electronic Medical Record System “BH-PL Program” is a program that facilitates medical by saving the patient's history data directly into the computer system, collecting data completely according to standards, meet the needs of information users and data owner and supporting the development of patient services. It is a development of advances in information technology of Buddhachinaraj Hospital, Phitsanulok with the objectives 1) to develop electronic medical records (EMRs) 2) to test the system and study the satisfaction of using the BH-PL program 3) to bring the results of the study to expand the results of EMRs recording usage through the entire wards in our hospital. By using the concept of System Development Life Cycle: SDLC to develop electronic medical records (EMRs), from the trial of electronic outpatient medical records in 2016 to electronic medical records (EMRs) for inpatients in COVID-19 in 2020 and expanding the recording of in-patient EMRs covering all wards in the hospital since 2023. This is extending the development of in-patient EMRs recording to cover all wards. Opinions of doctors and nurses on the use of the BH-PL program of 388 copies of 18 wards between October 2022 to March 2023 in all 5 aspects, namely ease of use and record, ease of searching reduce recording time, ease of access to the program and overall satisfaction of users were 3.3 0.8, 3.5 0.9, 3.7 1.0, 3.4 1.0 and 3.3 0.9 respectively (from a full score of 5). Recording data through the BH-PL program in the part of nursing records, preoperative patient records, patient discharge summaries and health assessment at the reception were equal to 100, 100, 100, 88.9, respectively. The use of EMRs by doctors and nurses through the BH-PL program was 100 percent, including San Suk ward, MIS ward, neurosurgery intensive care unit. Satisfaction in recording EMRs through the BH-PL program was moderate. Nurses are the group that uses this program almost entirely. while other medical and interdisciplinary groups are still used relatively little. A clear policy formulation from the hospital leadership team and an understanding of how users can see the benefits of recording EMRs with BH-PL should be a successful way to record EMRs. Reference กระทรวงเทคโนโลยีสารสนเทศและการสื่อสาร. (2557). (ร่าง) แผนแม่บทเทคโนโลยีสารสนเทศและสื่อสาร (ฉบับที่ 3) ของประเทศไทย, 35. สำนักงานเลขาธิการวุฒิสภาปฏิบัติหน้าที่สำนักงานเลขาธิการสภานิติบัญญัติแห่งชาติ. 6 มีนาคม 2562.ร่างพระราชบัญญัติซึ่งสภานิติบัญญัติแห่งชาติลงมติเห็นสมควรประกาศใช้เป็นกฎหมายฉบับที่ 3 : https://www.dga.or.th/wp - content/uploads/2021/02/4.pdf พลโท หม่อมหลวงสุปรีดี ประวิตร. (2561). โน้มน้าวทางความคิดให้ไปสู่ระบบสำนักงานไร้กระดาษเพื่อตอบสนองตามนโยบายไทยแลนด์ 4.0. วิทยาลัยป้องกันราชอาณาจักรสถาบันวิชาการป้องกันประเทศ. http://www.dsdw2016.dsdw.go.th/doc_pr/ndc_2560 -2561/PDF สำนักตรวจสอบการชดเชยและคุณภาพบริการ สำนักงานหลักประกันสุขภาพแห่งชาติ. คู่มือการตรวจประเมินคุณภาพการบันทึกเวชระเบียน. พิมพ์ครั้งที่ 1; กันยายน 2563. สมาคมเวชสารสนเทศไทย.ข้อเสนอขอสมาคมเวชสารสนเทศไทยเพื่อการปฏิรูประบบสารสนเทศสุขภาพไทยมุ่งสู่อนาคตต่อรัฐมนตรีว่าการกระทรวงการสาธารณสุข (ศ.นพ.รัชตะนาวิน); 2557. เกียรติพงษ์ อุดมธนะธีระ. วงจรการพัฒนาระบบ (System Development Life Cycle : SDLC) เผยแพร่ ; 15 มี.ค.2019 เลขรหัสเอกสารจากหน่วยเวชสารสนเทศ โรงพยาบาลพุทธชินราช พิษณุโลก. แบบฟอร์มเวชระเบียน. http://192.168.50.2/fileprocedure/ Mayuree Sukhupayalak, Somporn Jedsadayanmata, Ratchaneewan Rakkeitpao, Jutathip Sumritsuk, Pannee Chusri, Somsri Panpoi. การพัฒนารูปแบบการจัดการพยาบาล. พุทธชินราชเวชสาร. ปีที่ 35 ฉบับที่ 3 ; กันยายน 2561- ธันวาคม 2561